Reducing Sodium in Foods: The Effect on Flavor - Liem, Djin Gie (MDPI, 2011)
Sodium is an essential micronutrient and, via salt taste, appetitive. High consumption of sodium is, however, related to negative health effects such as hypertension, cardiovascular diseases and stroke. In industrialized countries, about 75% of sodium in the diet comes from manufactured foods and foods eaten away from home. Reducing sodium in processed foods will be, however, challenging due to sodium’s specific functionality in terms of flavor and associated palatability of foods (i.e., increase of saltiness, reduction of bitterness, enhancement of sweetness and other congruent flavors). The current review discusses the sensory role of sodium in food, determinants of salt taste perception and a variety of strategies, such as sodium replacers (i.e., potassium salts) and gradual reduction of sodium, to decrease sodium in processed foods while maintaining palatability.